2019
DOI: 10.1371/journal.pone.0210657
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the diagnosis and control of hypertension is not explained by conventional variables: Cross-sectional database study in English general practice

Abstract: BackgroundHypertension is a major cause of preventable disability and death globally and affects more than one in four adults in England. Unwarranted variation is variation in access, quality, outcome or value which is unexplained by differences in the condition or patient characteristics and which reduces quality and efficiency. Distinguishing unwarranted from variation due to clinical, organisational or patient factors can be challenging. We carried out this study to explore inter-practice variation in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Large primary care databases have been used before for measuring prescription rates and general practitioner (GP) variability in prescribing, but analyses have generally been limited to specific medication classes (e.g., antibiotics or opioids) ( Guthrie et al, 2015b ; Haastrup et al, 2016 ; Coyle et al, 2019 ) or populations (e.g., older patients) ( Aubert et al, 2016 ; Schnegg et al, 2020 ). Comprehensive assessments across all medication classes and patient demographics are needed to identify the specific medication classes contributing to polypharmacy and to develop targeted initiatives to improve prescribing practices.…”
Section: Introductionmentioning
confidence: 99%
“…Large primary care databases have been used before for measuring prescription rates and general practitioner (GP) variability in prescribing, but analyses have generally been limited to specific medication classes (e.g., antibiotics or opioids) ( Guthrie et al, 2015b ; Haastrup et al, 2016 ; Coyle et al, 2019 ) or populations (e.g., older patients) ( Aubert et al, 2016 ; Schnegg et al, 2020 ). Comprehensive assessments across all medication classes and patient demographics are needed to identify the specific medication classes contributing to polypharmacy and to develop targeted initiatives to improve prescribing practices.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of 3 health systems participating in the San Francisco Bay Collaborative Research found the percentage of patients in control varied by as much as 32% across sites 30. A study in Great Britain identified that smaller practice size was associated with uncontrolled BP; however, much of the variation was uncharacterized 31. We found patient demographics and chronic conditions accounted for only a small amount of the variation in site-specific control.…”
Section: Discussionmentioning
confidence: 66%
“…30 A study in Great Britain identified that smaller practice size was associated with uncontrolled BP; however, much of the variation was uncharacterized. 31 We found patient demographics and chronic conditions accounted for only a small amount of the variation in site-specific control. Other potential explanations for the differences observed across locations that we could not explore in our analysis include variations in medication adherence and refractory hypertension.…”
Section: Discussionmentioning
confidence: 76%
“…The classification of features is shown in Figure 1 Race and ethnicity 18 (39) 18 [9][10][11][12][13][14][15]17,21,23,28,29,[35][36][37][38]45,49 Social Socioeconomic status 30 (65) 30 [9][10][11][12][13][14][15][16] Social risk factors 12 (26) 12 [10][11][12][13][14][15][16][18][19][20][21]45 Clinical characteristics Patient profile N/A Body mass index 7 (15) 7 20,23,34,[39][40][41]49 History Comorbidity 29 (63) 29 [9][10][11]13,[15]…”
Section: Feature Categoriesmentioning
confidence: 99%
“…The standard indices include Australia's Socioeconomic Indexes for Areas (SEIFA), 22 and Index of Relative Socioeconomic Disadvantage (IRSD), 16 the UK's Index of Multiple Deprivation (IMD). [23][24][25][26][27] The ad hoc measures include income levels, 11,12,15,19,[28][29][30][31][32][33] education levels, 11,15,28,34 neighbourhood income or rural setting, 15,19,20,35 non-English speakers, 18 and insurance type. [12][13][14][15][16]21,[35][36][37][38]…”
Section: Sociodemographic Featuresmentioning
confidence: 99%